5000 Free Flaps and Counting: A 10-Year Review of a Single Academic Institution's Microsurgical Development and Outcomes. Issue 4 (April 2018) - Carney, Martin J.; Weissler, Jason M.; Tecce, Michael G.; Mirzabeigi, Michael N.; Wes, Ari M.; Koltz, Peter F.; Kanchwala, Suhail K.; Low, David W.; Kovach, Stephen J.; Wu, Liza C.; Serletti, Joseph M.; Fosnot, Joshua
Abstract : Background: The establishment of an effective clinical and academic culture within an institution is a multifactorial process. This process is cultivated by dynamic elements such as recruitment of an accomplished and diverse faculty, patient geographic outreach, clinical outcomes research, and fundamental support from all levels of an institution. This study reviews the academic evolution of a single academic plastic surgery practice, and summarizes a 10-year experience of microsurgical development, clinical outcomes, and academic productivity. Methods: A 10-year retrospective institutional review was performed from fiscal years 2006 to 2016. Microsurgical flap type and operative volume were measured across all microsurgery faculty and participating hospitals. Microvascular compromise and flap salvage rates were noted for the six highest volume surgeons. Univariate and multivariable predictors of flap salvage were determined. Results: The 5000th flap was performed in December of 2015 within this institutional study period. Looking at the six highest volume surgeons, free flaps were examined for microvascular compromise, with an institutional mean take-back rate of 1.53 percent and flap loss rate of 0.55 percent across all participating hospitals. Overall, 74.4 percent of cases were breast flaps, and the remaining cases were extremity and head and neck flaps. Conclusions: Focused faculty and trainee recruitment has resulted in an academically and clinically productive practice. Collaboration among faculty, staff, and residents contributes to continual learning, innovation, and quality patient care. This established framework, constructed based on experience, offers a workable and reproducible model for other academic plastic surgery institutions. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.